Development of an Immunoassay for the Kidney-Specific Protein myo-Inositol Oxygenase, a Potential Biomarker of Acute Kidney Injury. (1st May 2014) - Gaut, Joseph P; Crimmins, Dan L; Ohlendorf, Matt F; Lockwood, Christina M; Griest, Terry A; Brada, Nancy A; Hoshi, Masato; Sato, Bryan; Hotchkiss, Richard S; Jain, Sanjay; Ladenson, Jack H
Abstract: BACKGROUND: Acute kidney injury (AKI) affects 45% of critically ill patients, resulting in increased morbidity and mortality. The diagnostic standard, plasma creatinine, is nonspecific and may not increase until days after injury. There is significant need for a renal-specific AKI biomarker detectable early enough that there would be a potential window for therapeutic intervention. In this study, we sought to identify a renal-specific biomarker of AKI. METHODS: We analyzed gene expression data from normal mouse tissues to identify kidney-specific genes, one of which was Miox . We generated monoclonal antibodies to recombinant myo -inositol oxygenase (MIOX) and developed an immunoassay to quantify MIOX in plasma. The immunoassay was tested in animals and retrospectively in patients with and without AKI. RESULTS: Kidney tissue specificity of MIOX was supported by Western blot. Immunohistochemistry localized MIOX to the proximal renal tubule. Serum MIOX, undetectable at baseline, increased 24 h following AKI in mice. Plasma MIOX was increased in critically ill patients with AKI [mean (SD) 12.4 (4.3) ng/mL, n = 42] compared with patients without AKI [0.5 (0.3) ng/mL, n = 17] and was highest in patients with oliguric AKI [20.2 (7.5) ng/mL, n = 23]. Plasma MIOX increased 54.3 (3.8) h before the increase in creatinine. CONCLUSIONS: MIOX is a renal-specific, proximal tubule protein that is increased in serum of animals and plasma of critically ill patients with AKI. MIOX preceded the increases in creatinine concentration by approximately 2 days in human patients. Large-scale studies are warranted to further investigate MIOX as an AKI biomarker.